Polymerisations in supercritical carbon dioxide - Bassett, Simon (2015)
This Thesis describes the use of supercritical carbon dioxide as both a reaction solvent and processing medium for synthesis new polymeric materials. Chapter 2 details the high pressure equipment used for this body of work, as well as the analytical techniques employed. This includes equipment details for a new high pressure cell designed for measuring small angle x-ray scattering of polymers in situ. Chapter 3 describes the homopolymerisation of both methyl methacrylate and styrene in a supercritical carbon dioxide expanded phase system. Effects of molecular weight and viscosity on the final reaction product are probed in order to ascertain the most suitable types of polymers to be synthesised by this method. This is then extended to create low molecular weight block copolymers in the absence of any volatile organic solvents, with comparable properties to those produced by conventional methods. The development of the high pressure cell for measuring small angle x-ray scattering of block copolymers synthesised in a supercritical carbon dioxide dispersion polymerisation in situ is described in Chapter 4. Initial investigations showed problems with the synthesis in this new vessel, with different products obtained compared to a conventional autoclave. However, data is presented to display the suitability of certain aspects of the design and that scattering patterns can be acquire in situ during a polymerisation. Details of a second modified design are presented, with construction currently in progress. Finally, a green synthetic route to producing renewable, biodegradable and biocompatible polymers is presented in Chapter 5. By using supercritical carbon dioxide to lower the melting temperatures of the monomers, polymerisations usually conducted at temperatures in excess of 130 °C were successfully conducted at 80 °C. Through the use of a novel zirconium catalyst the tacticity of poly(lactic acid) was controlled, opening up a route to functional materials.